2020
DOI: 10.3311/ppme.13507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pixel-based Position Input and Direct Acceleration Input for Virtual Stick Balancing Tests

Abstract: A virtual stick balancing environment is developed using a computer mouse as input device. The development process is presented both on the hardware and software level. Two possible concepts are suggested to obtain the acceleration of the input device: discrete differentiation of the cursor position measured in pixels on the screen and by direct measurements via an Inertial Measurement Unit (IMU). The comparison of the inputs is carried out with test measurements using a crank mechanism. The measured signals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Due to the finite number of pixels, this results in a noisy acceleration signal. Therefore, a simple re-sampling filter was used, and the input acceleration was computed asanormalSfalse(tifalse)=Kx(ti)2x(tik)+x(ti2k)Δt2,where K = 8.85 × 10 −5 m/pixel is a gain factor scaling the screen size to the manipulation length of the computer mouse [44], x ( t i ) is the mouse position measured in pixels at the time instant t i = i Δ t and k ≥ 1 is an integer filtering parameter. The sampling period was set to Δ t = 16.67 ms, which corresponds to the screen refresh rate 60 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the finite number of pixels, this results in a noisy acceleration signal. Therefore, a simple re-sampling filter was used, and the input acceleration was computed asanormalSfalse(tifalse)=Kx(ti)2x(tik)+x(ti2k)Δt2,where K = 8.85 × 10 −5 m/pixel is a gain factor scaling the screen size to the manipulation length of the computer mouse [44], x ( t i ) is the mouse position measured in pixels at the time instant t i = i Δ t and k ≥ 1 is an integer filtering parameter. The sampling period was set to Δ t = 16.67 ms, which corresponds to the screen refresh rate 60 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…For the actuation of the virtual environment, the input signal is the acceleration of the computer mouse moved by the subject's hand. The acceleration was determined via numerical derivation of the pixel-based position of the cursor [44]. Due to the finite number of pixels, this results in a noisy acceleration signal.…”
Section: Virtual Stick Balancing Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The tests can run on a computer, a tablet PC or a smart phone [23][24][25], however the set-ups which use monitors or any kind of digital displays suffer from the unknown latency: the object appear on the screen with unknown delay. The results in [26] shows that the time delay is typically in the range of 30-100 ms depending of the manufacturer and type of the display, and it is also shown that the delay changes stochastically. Regarding to the delay problem, the online tests are the worst, where the server-client communication is an additional stochastic latency.…”
Section: Reaction Time Testers From the Literaturementioning
confidence: 97%
“…x of the input device. Both the velocity and the acceleration of the subject's hand movement were determined by a numerical derivation scheme based on the pixel position of the cursor on the screen [20,30]. Owing to the finite size of the pixels, the numerical derivation results in a noisy signal, which was compensated by a resampling filter.…”
Section: Virtual Test Environmentmentioning
confidence: 99%